EXPLORING THE ECONOMIC IMPACTS OF SUSTAINABLE TOURISM ON LOCALS: A COMPARATIVE ANALYSIS BETWEEN BALI AND NORTH SUMATERA - Diego Romario De Fretes; Caroline Caroline; Al- Amin; Swanto Sirait; Ahmad Rizani (ADISAM PUBLISHER, 2023)
This comparative analysis explores the economic impacts of sustainable tourism on local communities in Bali and North Sumatra, Indonesia. The study highlights the significance of understanding the specific contexts of these regions and examines the economic benefits, challenges, and policy initiatives related to sustainable tourism development. The research methodology involved a comprehensive literature review and data analysis. The selection criteria for comparative analysis and the variables and indicators used were carefully considered to ensure a comprehensive examination of the economic impacts of sustainable tourism in Bali and North Sumatra. The findings reveal positive economic outcomes in both regions, including job creation, income generation, and support for local businesses. However, Bali exhibits a more significant economic impact with its more developed tourism industry than North Sumatra. This difference can be attributed to factors such as higher tourist influx and better tourism infrastructure in Bali. The comparative analysis also uncovers common challenges locals face in both regions, including infrastructure development, resource management, cultural preservation, community engagement, capacity building, marketing strategies, and equitable distribution of benefits. Addressing these challenges is essential for sustaining the economic benefits of sustainable tourism and ensuring the preservation of natural and cultural resources. In conclusion, this comparative analysis highlights the economic impacts of sustainable tourism in Bali and North Sumatra. It emphasizes the need to address challenges and implement effective policies to maximize economic benefits and ensure a more equitable distribution for local communities.